Intuitive Spatial Tactile Feedback for Better Awareness about Robot Trajectory during Human-Robot Collaboration - Grushko, Stefan; Vysocký, Aleš; Heczko, Dominik; Bobovský, Zdenko (Sensors (Basel, Switzerland), 2021)
In this work, we extend the previously proposed approach of improving mutual perception during human-robot collaboration by communicating the robot's motion intentions and status to a human worker using hand-worn haptic feedback devices. The improvement is presented by introducing spatial tactile feedback, which provides the human worker with more intuitive information about the currently planned robot's trajectory, given its spatial configuration. The enhanced feedback devices communicate directional information through activation of six tactors spatially organised to represent an orthogonal coordinate frame: the vibration activates on the side of the feedback device that is closest to the future path of the robot. To test the effectiveness of the improved human-machine interface, two user studies were prepared and conducted. The first study aimed to quantitatively evaluate the ease of differentiating activation of individual tactors of the notification devices. The second user study aimed to assess the overall usability of the enhanced notification mode for improving human awareness about the planned trajectory of a robot. The results of the first experiment allowed to identify the tactors for which vibration intensity was most often confused by users. The results of the second experiment showed that the enhanced notification system allowed the participants to complete the task faster and, in general, improved user awareness of the robot's movement plan, according to both objective and subjective data. Moreover, the majority of participants (82%) favoured the improved notification system over its previous non-directional version and vision-based inspection.
Keywords: uživatelské rozhraní počítače; Robotics; human–robot collaboration; hmat; human–machine interface; ruka; Touch; human–robot interaction; Humans; Feedback; lidé; User-Computer Interface; mutual awareness; zpětná vazba; haptic feedback device; spatial tactile feedback; Hand; robotika